St. Anna Marie's Convent: Wichita, Kansas - Dan Himmelberg (Oz, 1986)
Located on a picturesque site on the secluded northern shore of Cheney Lake, St. Anna Marie's serves as the Mother House Convent for the Sisters of the Most Precious Blood. After the existing St. Louis facility was destroyed by fire and because of its diminishing numbers, the congregation elected to merge with its sister convent in Wichita, Kansas...